Engagement: A Necessary Ingredient for Participation in Adult Basic Education - Mary Ziegler; Chas Durant (Adult Education Research Conference, 2001)
Education plays varying roles in efforts to reform the nation's welfare system. Some states provide adult basic education as a precursor to employment and career advancement. This study examined psychological and programmatic factors impacting this group of participants in adult basic education. Engagement was found to be a key variable.